Observations on the colon bacillus - Rebagliati, Raúl (1923)
The concept of the pathogenic role of the bacterium coli wins - since the first description of the germ to make Escherich - a series of vicissitudes. Sometimes exaggerated, denied others, has been the emphasis desmedrandose regular guest of this organism and, between us, hardly gives any pathogenicity. In recent years I have had the opportunity to test the pathogenic action of the colon bacillus in various abnormal states, in terms that deserve attention.